Integrasi Iptek Dengan Imtaq pada Pelajaran MIA di MAN Insan Cendekia Tapanuli Selatan - Maratua Harahap; Muhammad Darwis Dasopang (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2020)
The dichotomy of science in madrasa, science and technology material has not been integrated with Islam and vice versa. Habibie founded Insan Scholar to unite IPTEK with IMTAQ, and MAN IC South Tapanuli was no exception. This study aims to describe, discover, and explain the integration of IPTEK white IMTAQ of MIA subject groups in MAN Insan Cendekia South Tapanuli. The conclusions of this study are: The curriculum integration implemented at MAN Insan Cendekia South Tapanuli is the development of a curriculum set by the government. There are two patterns used by teachers in curriculum integration, namely Islamization of general science, and Spiritualization of learning. This can be seen from the integration steps contained in the plan, implementation, and evaluation of the program, namely: 1) Read greetings and prayers, 2) Apperception and ensure students memorize Qur’an and Hadith, 3) Review material from a general and Islamic angle, 4) Bringing students out of the room for natural learning, 5) Providing exercises and questions that can improve IPTEK and IMTAQ, 6) Motivation and re-awareness that all truth comes from God, 7) Closed with Kafaratul Majelis prayers and greetings.